"School within a school": Examining implementation barriers in a Spanish/English transitional bilingual education program. Issue 2 (2nd April 2016) - DeNicolo, Christina Passos
ABSTRACT: This article explores the ways that general education and bilingual teachers make sense of a Spanish/English transitional bilingual program housed at one elementary school in a Midwestern school district. An in-depth examination of perceptions and attitudes unmasks key factors regarding the implementation and interpretation of bilingual programs and how these factors impact school climate and the overall functioning of the program. Primary themes indicated that the use of specific terms, such as "school within a school, " exacerbated the sense of division between the general education and bilingual programs, adding to the challenges of achieving opportunities for bringing students together across programs.